2005
DOI: 10.1103/physrevb.72.241402
|View full text |Cite|
|
Sign up to set email alerts
|

Exciton binding energies in carbon nanotubes from two-photon photoluminescence

Abstract: Excitonic effects in the linear and nonlinear optical properties of single-walled carbon nanotubes are manifested by photoluminescence excitation experiments and ab initio calculations. One- and two-photon spectra showed a series of exciton states; their energy splitting is the fingerprint of excitonic interactions in carbon nanotubes. By ab initio calculations we determine the energies, wave functions, and symmetries of the excitonic states. Combining experiment and theory we find binding energies of 0.3–0.4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
304
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(327 citation statements)
references
References 32 publications
19
304
3
1
Order By: Relevance
“…Many experiments demonstrated that optical transitions in CNTs arise from excitons with strong binding energy [26][27][28] even for relatively large diameters and higher-order energy transitions 10 . Each of these optical resonances is referred to as S ij or M ij , depending on the nature of the nanotube (S for semiconducting and M for metallic) and the corresponding valence (i) and conduction (j) sub-band in the single-particle band model.…”
Section: Resultsmentioning
confidence: 99%
“…Many experiments demonstrated that optical transitions in CNTs arise from excitons with strong binding energy [26][27][28] even for relatively large diameters and higher-order energy transitions 10 . Each of these optical resonances is referred to as S ij or M ij , depending on the nature of the nanotube (S for semiconducting and M for metallic) and the corresponding valence (i) and conduction (j) sub-band in the single-particle band model.…”
Section: Resultsmentioning
confidence: 99%
“…Nanotube isolation is critical due to the presence of both m-and s-CNTs in the solution and the tendency to form bundles, which causes radiationless intertube carrier transfer [204]. Photoluminescence excitation (PLE) allows not only to verify the presence of single-walled carbon nanotubes in a sample but also to determine the geometry of s-CNTs with a high accuracy, study their electronic and optical properties, interactions of single nanotubes in bundles [49] and with the environment [205].…”
Section: Photoluminescence Excitationmentioning
confidence: 99%
“…However, a recent photoluminescence study of small bundles in solution shows that exciton energy transfer between semiconducting SWNTs within bundles can be an efficient carrier relaxation channel [47]. The multicomponent carrier recombination dynamics inherent to nanotubes comes from (i) intraband thermalisation (with relaxation time of 200 fs) [48], (ii) exciton energy transfer between adjacent tubes in bundles [47], (iii) nonradiative recombination through dark excitonic states and excited carrier tunnelling on metallic tubes (m-CNTs) (500 fs-10 ps) and (iv) the radiative recombination through bright excitonic states (10-500 ps) [41,49].…”
Section: Introductionmentioning
confidence: 99%
“…7͒ are 1D materials that possess various unique properties. 8 The strong confinement in the radial direction ͑ϳ1 nm͒ and the weak dielectric screening inside SWNTs give rise to very large exciton binding energies of ϳ0.5 eV, [9][10][11][12][13] which is much larger than those of InGaAs quantum wires 5,14 and larger than or comparable to those of -conjugated polymers. 15,16 So far, various groups have studied the ex-ph interactions in SWNTs both in terms of theory 17,18 and experiment [19][20][21][22] and have revealed the existence of a phonon sideband approximately 200 meV above the energy level of the singlet bright exciton ͑which has an s envelope and termed a "1u" state based on symmetry 12,13 but we simply call it "E ii " hereafter for the ith single-particle subband͒.…”
Section: Introductionmentioning
confidence: 99%